Kasautumisen vaikutus tuottavuuteen: Työpaikkojen välisen aavutettavuuden vaikutus toimipaikkoihin ja työntekijöihin - Taina Haapamäki; Oskari Harjunen; Antti Kauhanen; Veeti Kuivalainen; Krista Riukula; Nelli Valmari; Touko Väänänen (The Research Institute of the Finnish Economy (ETLA), 2024)
– In economics, the regional densification of economic activity is referred to as agglomeration. The effects of agglomeration are often referred to when discussing the wider economic benefits of transportation infrastructure projects. The magnitude of these effects has not been extensively studied in Finland. In this report, we examine the impact of agglomeration on productivity in the Helsinki region, utilizing extensive registry data. We find that improved job to job accessibility increases employees' wages. However, our findings concerning the value-added at establishment level are less conclusive and statistically insignificant. Our results suggest that increased accessibility leads to increases in other operating expenses such as rents, potentially explaining the lack of statistically significant effect on value-added. Our results suggest that agglomeration benefits are predominantly intraregional, with interregional accessibility having little impact on these benefits. Thus, the ratio between the agglomeration benefits and the direct benefits of transportation infrastructure projects varies depending on the project. Including these benefits directly to cost-benefit analyses risks double counting some benefits. Taxes and similar payments on increased wages due to accessibility increases could be included as a separate item in the cost-benefit analysis.
Keywords: R41; R42; R12; 330; Agglomeration; Productivity; Transport project; Cost-benefit analysis; Accessibility; Wider economic impacts